2008
DOI: 10.1161/circulationaha.108.189702
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Prevention of Obesity

Abstract: Abstract-Obesity is a major influence on the development and course of cardiovascular diseases and affects physical and social functioning and quality of life. The importance of effective interventions to reduce obesity and related health risks has increased in recent decades because the number of adults and children who are obese has reached epidemic proportions. To prevent the development of overweight and obesity throughout the life course, population-based strategies that improve social and physical enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
272
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 544 publications
(281 citation statements)
references
References 402 publications
(327 reference statements)
4
272
1
4
Order By: Relevance
“…This is consistent with the emerging paradigm that contextual factors influence individual behaviour related to obesity, and that more available energy could lead to greater energy intake (17) .…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the emerging paradigm that contextual factors influence individual behaviour related to obesity, and that more available energy could lead to greater energy intake (17) .…”
Section: Discussionsupporting
confidence: 88%
“…For example, prior population‐wide intervention studies of salt reduction demonstrated decreases in morbidity, mortality, and healthcare costs with as little as 1 g less of salt per day (equivalent to 1/6 of a teaspoon)15 and are feasible, as evidenced by recent dietary salt reduction programs in the United Kingdom focused on manufactured food that decreased mean sodium content in the food supply by 7% 13. Other potential lifestyle interventions to reduce blood pressure include increasing physical activity,45, 46 reducing weight,47 and improving overall diet quality 46. Further studies are needed to inform safety48, 49 and selection of the most cost‐effective population‐wide interventions in the United States to decrease SBP.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of effective interventions to reduce obesity and related health risks has increased in recent decades due to obesity's epidemic proportions (53) . There are many challenges in executing and evaluating the effects of comprehensive school-and community-based interventions.…”
Section: Discussionmentioning
confidence: 99%